Strategi Komunikasi Humas Polres Karanganyar Dalam Kampanye Anti Hoaks Pilkada 2024 Melalui Instagram - Destika Wahyu Pratiwi; Esfandani Peni Indreswari; Rahmat Wisudawanto (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
This study discusses the communication strategy implemented by the Karanganyar Police Public Relations Department in delivering an anti-hoax campaign during the 2024 Regional Head Election (Pilkada) through the Instagram platform. The background of this study departs from the phenomenon of the rampant spread of false information ahead of the election, which has the potential to trigger disinformation, polarization, and disrupt social order and stability. Hoaxes during political periods can erode public trust in state institutions, so strategic efforts are needed to address this through effective public communication. The purpose of this study is to analyze the effectiveness of the digital communication strategy used by the Karanganyar Police Public Relations Department in increasing public literacy, encouraging public participation, and maintaining the quality and stability of information circulating in the digital space. This study uses a descriptive qualitative method with data collection techniques through in-depth interviews with Public Relations personnel, direct observation of campaign activities on Instagram, and documentation of published content. The strategy analysis refers to the Cutlip, Center, and Broom model which includes four stages: fact-collecting, planning, implementing communication actions, and evaluation. The results show that the use of Instagram was chosen because of its ability to reach a young audience, the flexibility of content formats, and opportunities for two-way interaction. The campaign content was dominated by educational materials presented visually through infographics, digital posters, and short videos, ensuring the anti-hoax message was clearly and persuasively conveyed and easily shared by users. Evaluations showed an increase in public engagement, including comments, content sharing, and participation in online discussions, as well as a significant decrease in the number of hoax reports circulating in the Karanganyar region during the campaign period. This study recommends optimizing the use of Instagram features such as live broadcasts, reels, and interactions through polls or quizzes, along with increasing the creativity of the Public Relations team to further enhance the effectiveness of digital public communication in the future.